Development of Problem-Based Independent Curriculum Physics Teaching Module to Improve Students' Critical Thinking Skills - Arham Indrawati; Muhammad Arsyad; Ahmad Yani (Postgraduate, University of Mataram, 2026)
This research aims to: design a problem-based independent curriculum physics teaching module to improve students' critical thinking skills that meet valid criteria; design a problem-based independent curriculum physics teaching module to improve students' effective critical thinking skills based on teacher practitioner assessments; design a problem-based independent curriculum physics teaching module to improve students' critical thinking skills effective based on the assessment of student practitioners; analyzing the effectiveness of the use of the problem-based independent curriculum physics teaching module to improve the critical thinking skills of students of SMA Negeri 3 Makassar City that has been developed. The method used to achieve this goal is R&D using the development of 4D models. The sample of this study is 38 00 students and 10 physics teachers in Makassar city. The instruments used in this study were module validation sheets, practitioner assessment questionnaires, and students' critical thinking ability test instruments. Based on the results of the analysis, it was obtained that: the independent problem-based curriculum physics teaching module developed based on expert assessments was declared valid and suitable for use with a slight revision; the physics teaching module of the independent problem-based curriculum reviewed from the teacher's response for all aspects obtained an average score percentage of 85% at the very good criterion; the problem-based independent curriculum physics teaching module reviewed from the students' responses for all aspects obtained an average score percentage of 86% on the very good criteria; The effectiveness of the use of problem-based physics teaching modules was obtained from the results of the students' critical thinking ability test that was effectively used with an N-gain score of 0.84 ≥ 0.70, with a high category. From the results of the analysis, it can be concluded that the problem-based physics teaching module developed is valid, practical, and effective to improve students' critical thinking skills in physics learning.